DETERMINAN BELANJA MODAL PEMERINTAH KABUPATEN DAN KOTA DI SUMATERA SELATAN - Maria Maria (JURNAL RISET TERAPAN AKUNTANSI, 2017)
The purpose of this research was to test the effect of Local Goverment Revenue (LGR), Balancing Funds (BF), and Financing  Surplus  Budget  (FSB)simultaneously  or  partially  to  Capital  Expenditure  (CE).The  object  of  this research are the 15 districts and cities in South Sumatera which have published their reportson the period of 2012- 2015.The data collection  in  this research  used  documentation  technique.Data  analysiswas descriptive with statistic multiple regression,software SPSS 22.The result of research showed:LGR, BF, and FSBhad positive and significant effect towardCE with contribution of 86,4%. Partially, LGR and FSB hadn’t effect toward CE, BFhad positive and significant effect towardCE 18,83%.